Concise Review: Forkhead Pathway in the Control of Adult Neurogenesis. (23rd May 2014) - Genin, Emmanuelle C.; Caron, Nicolas; Vandenbosch, Renaud; Nguyen, Laurent; Malgrange, Brigitte
Abstract: New cells are continuously generated from immature proliferating cells in the adult brain in two neurogenic niches known as the subgranular zone (SGZ) of the dentate gyrus (DG) of the hippocampus and the sub-ventricular zone (SVZ) of the lateral ventricles. However, the molecular mechanisms regulating their proliferation, differentiation, migration and functional integration of newborn neurons in pre-existing neural network remain largely unknown. Forkhead box (Fox) proteins belong to a large family of transcription factors implicated in a wide variety of biological processes. Recently, there has been accumulating evidence that several members of this family of proteins play important roles in adult neurogenesis. Here, we describe recent advances in our understanding of regulation provided by Fox factors in adult neurogenesis, and evaluate the potential role of Fox proteins as targets for therapeutic intervention in neurodegenerative diseases. Stem Cells 2014;32:1398–1407